Deadly Diarrhea Caused by Co-Infection of Clostridium perfringens Type ST-865 and Clostridium difficile: A Case Report and Review of the Literature - Hao Y; Li J; Xie S; Liu Y; Wen H (Infection and Drug Resistance)
Yuyao Hao,1,* Jianhui Li,2,* Shoujun Xie,1 Yanchao Liu,1 Hainan Wen1,3 1Department of Clinical Laboratory, The Affiliated Hospital of Chengde Medical University, Chengde, Hebei, People’s Republic of China; 2Department of Preventive Medicine, Chengde Medical University, Chengde, Heibei, People’s Republic of China; 3Hebei Key Laboratory of Panvascular Diseases, The Affiliated Hospital of Chengde Medical University, Chengde, Heibei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hainan Wen, Email wenhainan0525@sina.comPurpose: There is a paucity of evidence regarding the occurrence of fatalities resulting from diarrhea due to co-infection with C. perfringens and C. difficile. Here, we report a rare case of severe diarrhea caused by a novel ST-865 type of C. perfringens in conjunction with C. difficile to draw the attention of clinicians and microbiology laboratory staff.Case Descriptions: The patient is male, 69 years old and one month before admission, there was diarrhea without fever. The doctor administered anti-infective treatments such as levofloxacin, ceftriaxone, minocycline, gentamicin and tinidazole, and sent fecal samples for anaerobic culture. Two colonies, Clostridium perfringens and Clostridium difficile, were cultivated and identified by sequencing as type F-Clostridium perfringens of ST-865 and Clostridium difficile carrying toxins A and B.Conclusion: The case we reported, which involved a severe case of diarrhea caused by a combined infection of ST-865 type F-type Clostridium perfringens and Clostridium difficile carrying both A and B toxins, and resulting in eventual death, is extremely rare. Such cases should draw the attention of clinicians and microbiology laboratory personnel.Keywords: Clostridium perfringens, Clostridium difficile, diarrhea